Denture Cleansing the Natural Way: A Review - Shrestha, S; Shrestha, BR (Journal of Nepalese Prosthodontic Society, 2023)
Dentures are used to replace the missing teeth and are specially used by the elderly population. Though it helps in the function of digestion and improves the facial appearance, its cleansing should be given utmost importance. Denture hygiene, if unmaintained, leads not only to oral diseases but also to systemic diseases. The conventional cleansers come with a certain degree of side effects along with the high price. So the use of natural denture cleansers may be a boon.Various researches have shown the efficacy of the natural herbs in single or multi component form. Herbs are rich in phytotherapeutic compounds like polyphenols, flavonoids, aromatic compounds, organic acids, silica, resins, vitamins and tannins. This review highlights some of the researches validating the herbal way to clean the denture cleansers and keep the oral cavity healthy. Most of the herbs used contain a number of antioxidants and may further enhance the immunity system and boost the systemic health as well. Hence, backed with proper evidences through researches, herbal denture cleansers may be a readily available tool for cleansing dentures and a promising source of generating healthy smiles of the elderly.